THE USE OF SIMULATED PATIENT IN ONLINE SELF-MEDICATION PRACTICE IN PHARMACY EDUCATION - Jihan, Jihan; Hidayah, Rachmadya Nur; Widyandana, Widyandana (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2023)
Background: The use of simulated patients on pharmacy education in Indonesia very rare, where most of the use of simulated patients is only to evaluate the performance of practicing pharmacists in the workplace and students during exams. Whereas use of simulated patients can improve performance students dealing with patients. This study wanted to see the impact of using simulated patients on the learning process in pharmacy education by online self-medication practice with assessed using the QuEST SCHOLAR instrument.Method: Study design on this research was quasi experimental with pretest–posttest in single group. The approach of this study using mix method with sequential explanatory design. The quantitative data was pretest and postest performance student, where assessed using the QueST SCHOLAR instrument and then analyzed using paired t-test, while the qualitative data explaining the impact of using simulated patients and peer to performance students choose based on maximum variation sampling to do in depth interview with semi structured questions then transcribed and coding by two coder.Results: Quantitative results have a significant change when performing role play with simulated patients, as evidenced by the results of the paired t-test with simulated patients that is equal to 0.00 value. According to student perceptions, students prefer role play with simulated patients than with peers because the simulated patient is like a real patient and provides feedback so that students know their weaknesses and can boost their self-confidence.Conclusion: The performance of students has increased as a result of the usage of simulated patients in pharmacy education.